(untitled) (Palíndromo, 2022)
Starting from its own biography and as Artistic Education teacher in Educators, Teacher´s Training and in the Visual Arts, this article aims to critically analyze the changes occurred in Portugal in the last 4 decades at the University education on the Visual Arts field and on the artistic system, with the objective of comprehend the factors and circumstances which impact on the Art Teacher profile as well on the teaching of Art. The succinct compilation of data on the educational offer in the field of Visual Arts and the analysis of the interdependencies between artistic phenomena and the system in which they are inserted, allows us to conclude an inevitable change in the profile of the art teacher as well as in the paradigm of artistic creation.